Constraints on the Nonstandard Interaction in Propagation from Atmospheric Neutrinos - Shinya Fukasawa; Osamu Yasuda (Advances in High Energy Physics)
The sensitivity of the atmospheric neutrino experiments to the nonstandard flavor-dependent interaction in neutrino propagation is studied under the assumption that only nonvanishing components of the nonstandard matter effect are the electron and tau neutrino components ϵee, and ϵeτ, ϵττ and that the tau-tau component satisfies the constraint ϵττ=|ϵeτ|2/(1+ϵee) which is suggested from the high energy behavior for atmospheric neutrino data. It is shown that the Super-Kamiokande (SK) data for 4438 days constrains |tanβ|≡|ϵeτ/(1+ϵee)|≲0.8 at 2.5σ (98.8%) CL whereas the future Hyper-Kamiokande experiment for the same period of time as SK will constrain as |tanβ|≲0.3 at 2.5σCL from the energy rate analysis and the energy spectrum analysis will give even tighter bounds on ϵee and |ϵeτ|.